2010
DOI: 10.1089/lrb.2010.0009
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Pump Treatment Augments Lymphatic Flux of Lymphocytes in Rats

Abstract: Background: Lymphatic pump techniques (LPT) are used by osteopathic practitioners for the treatment of edema and infection; however, the mechanisms by which LPT enhances the lymphatic and immune systems are poorly understood. Methods and Results: To measure the effect of LPT on the rat, the cisterna chyli (CC) of 10 rats were cannulated and lymph was collected during 4 min of 1) pre-LPT baseline, 2) 4 min LPT, and 3) 10 min post-LPT recovery. LPT increased significantly (p < 0.05) lymph flow from a baseline of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 13 publications
0
37
0
Order By: Relevance
“…5,12 Previously, we demonstrated that a single application of LPT increased lymph flow and leukocyte flux in both rats and dogs, and mobilized inflammatory mediators into lymph circulation. [13][14][15][16][17][18][19] These findings support the use of LPT to treat edema and to enhance immune function. Importantly, the effects of LPT on the lymphatic system were transient, suggesting this LPT-sensitive lymph reservoir is limited.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…5,12 Previously, we demonstrated that a single application of LPT increased lymph flow and leukocyte flux in both rats and dogs, and mobilized inflammatory mediators into lymph circulation. [13][14][15][16][17][18][19] These findings support the use of LPT to treat edema and to enhance immune function. Importantly, the effects of LPT on the lymphatic system were transient, suggesting this LPT-sensitive lymph reservoir is limited.…”
Section: Introductionmentioning
confidence: 66%
“…17 In addition, LPT increased lymph flow and the mobilization of gastrointestinal lymphoid tissue derived leukocyte counts of both dogs and rats. 15,17 The aim of the present study was to gain new information on replenishment of LPT-sensitive lymph reservoirs by repeating LPT after a 2 h resting interval. We found both LPT 1 and LPT 2 produced similar increases in TDL flow, TDL leukocyte concentration, and the lymphatic flux of leukocytes and immune mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphatic pump techniques have been shown to increase cytokines and chemokines in thoracic and intestinal lymph vessels 35 , while mechanical pressure to certain body regions distant from the location of lymph formation enhances flow into lymphatic systems 36 . In addition, it has been shown that lymphatic OMT augments leukocyte mobilization and flow in dogs and rats, primarily from gut-associated lymphoid tissue 37,38,39,40,41 .…”
Section: Representative Resultsmentioning
confidence: 99%
“…3 Two articles in the current issue of Lymphatic Research and Biology strive to address this need. Working in a rat model, Huff and colleagues 8 have attempted to objectively investigate the mechanisms whereby lymphatic pump techniques purportedly enhance lymphatic and immune function. The implications of their observations are that the pneumatic technique may enhance immune surveillance by increasing the numbers of lymphocytes released into the lymphatic circulation, in particular from the gut-associated lymphoid tissue.…”
mentioning
confidence: 99%